Frisby Davis distance stereoacuity values in visually normal children. Issue 11 (18th October 2005) - Adams, W E; Hrisos, S; Richardson, S; Davis, H; Frisby, J P; Clarke, M P
Abstract : Aims: To establish the range of normal distance stereoacuity in young children using the Frisby Davis distance stereotest (FD2). Methods: Children passing preschool vision screening assessments underwent measurement of distance stereoacuity with the FD2 using a standard testing protocol. Results: 59 visually normal children aged between 36 months and 68 months were recruited to this study. All 59 were able to understand the test requirements and were examined with the FD2 stereotest. Four (6.8%) had no measurable stereoacuity; 13 (24%) had stereoacuity measurable only at a 3 metre testing distance (mean 92.3 seconds of arc; SD 52.6). These children were significantly younger than the remaining 42 (76%) who demonstrated a stereoacuity response at a 6 metre testing distance (mean 29.6 seconds of arc; SD 13.1, p = 0.008). Conclusion: The FD2 stereotest enables the measurement of distance stereoacuity in young children. There appears to be a maturational effect with distance stereoacuity improving between 36 months and 68 months. The data on age related normal values will provide a baseline from which to compare outcomes in clinical populations.